SBI INTEREST RATE EFFECT, THE VALUE OF U.S. DOLLAR EXCHANGE RATE, INFLATION RATE, TIME ON COMPOSITE STOCK PRICE INDEX (CSPI) - Asbarry, Chris; Sularto SE, MMSi, Dr. Lana (Accounting, 2009)
The interest rate of SBI in the last 3 years have seen fluctuations, this can be seen from the data obtained from Bank Indonesia from www.bi.go.id, where the SBI interest rate in January 2006 amounted to 12.74%, then decreases to 7.93 % in February 2007, and again rising up at 11:24% in December 2008. This is because the world economic recession at the end of 2008 yesterday. The more increase in SBI interest rate was no indication is triggered by low foreign exchange trading activity in this case the U.S. dollar. Fluctuations in foreign exchange trading value in this case the rupiah and U.S. dollar in the last three years proved to show very high fluctuations in January 2006 where the value of the rupiah against the U.S. Dollar is USD. 9560 and closed at the end of December 2006 amounted to Rp. 9520. In January 2007 the value of rupiah exchange rate was Rp. 9600 and closed at the end of December 2007 amounted to Rp. 9919, and in 2008 the value of the rupiah exchange rate against the dollar in January 2008 was Rp. 9826 and closed in December 2008 of Rp. 12 724. At the time of the most bullish of variables influence the value of deposits by 7359.612 units of JCI, and at most major bearish variables influence the value of inflation by 6317.426 units of JCI. Simultaneously, at the time of bullish or bearish variables (exchange rates, interest rate of Bank Indonesia Certificate, Inflation Rate, Deposit) had no significant effect on the index. Individually, when bullish variables that affect the exchange rate. Meanwhile, when bearish variables that influence the exchange rate, inflation, deposit. The proportion of the major influences on bullish namely deposits and the most influential is the Exchange and the SBI. The proportion of the major influences on inflation and the most bearish is no effect of SBI. Keywords : composite strock price index, cspi, sbi